The effect of the implementation of the health transformation plan on the health indicators of pregnant mothers in East Azerbaijan province, Iran: a longitudinal study from 2007 to 2016 - Hossein Jabbari Beirami; Parisa Yoshari; Davood Gharekhani; Elahe Ghorbani; Rahim Khodayari-Zarnaq (Payesh)
Objective(s): Maternal health indicators, especially for pregnant mothers, are among the most important health indicators for any country. Given the implementation of the health transformation plan in the service delivery system in Iran, it was expected that there would be a significant improvement in the quality and quantity of services provided to mothers in recent years. Therefore, the aim of this research was to investigate the effect of implementing healthcare reform on maternal health indicators in East Azerbaijan province, Iran. Methods: This was a quasi-experimental study. The research population consisted of people living in villages in East Azerbaijan province - Tabriz district, Iran; with active health centers from 2007 to 2016, including a sample size of 200 mothers per year. Villages were randomly selected as clusters. Data collection tool was a questionnaire and all data were analyzed by SPSS version 22 statistical software. Results: The findings showed that the mean age of mothers during the study period ranged from 25 to 27 years. The number of pregnancies before the reform was 1.39 and after the reform, it was 1.20 which was statistically significant. Examination of the insurance status of pregnant mothers showed that before the reform, 6.4% of rural residents were uninsured, while after the reform, all of them were covered. In terms of laboratory services, 97.7% of mothers underwent routine tests in the first trimester, and 90.5% underwent routine tests in the second trimester. Additionally, over 99% of mothers had undergone at least one ultrasound, with an average of 2.56 ultrasound appointments. Conclusion: The implementation of the healthcare reform increased the insurance coverage of pregnant mothers and the utilization of services such as ultrasound. This initiative led to a reduction in maternal and neonatal mortality rates and a decrease in the rate of natural childbirth.